Systematic review: Radiological and histological evidence of cochlear implant insertion trauma in adult patients. (4th July 2017) - Hoskison, Emma; Mitchell, Scott; Coulson, Chris
Abstract : Introduction : Cochlear implantation (CI) has developed from its origins in the 1980s. Initially, CI was for profound bilateral hearing impairment. However, candidacy for CI have become more widespread in recent years with unilateral implantation and an emphasis on hearing preservation. Evidence supports full electrode insertion in an atraumatic fashion into the scala tympani (ST) provides optimal hearing outcomes. The main aim of this systematic review was to elucidate the degree of trauma associated with CI insertion. Methods : A systematic literature search was undertaken using PubMed Medline. A grading system described by Eshraghi was used to classify cochlear trauma. Both radiological and histological studies were included. Results : Twenty one papers were identified which were relevant to our search. In total, 653 implants were inserted and 115 (17.6%) showed evidence of trauma. The cochleas with trauma had basilar membrane elevation in 5.2%, ruptured in 5.2%, the electrode passed from the ST to the SV in 84.4% and there was grade 4 trauma in 5.2%. The studies used a variety of histological and radiological methods to assess for evidence of trauma in both cadaveric temporal bones and live recipients. Conclusions : Minimizing cochlear trauma during implant insertion is important to preserve residual hearing and optimize audiological performance. An overall 17.6% trauma rate suggests that CI insertion could be improved with more accurate and consistent electrode insertion such as in the form of robotic guidance. The correlation of cochlea trauma with post-operative hearing has yet to be determined.